induction - Intermediate Mathematics Proof by Induction R...

Info iconThis preview shows pages 1–7. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Intermediate Mathematics Proof by Induction R Horan & M Lavelle The aim of this package is to provide a short self assessment programme for students who want to understand the method of proof by induction. Copyright c 2005 rhoran@plymouth.ac.uk , mlavelle@plymouth.ac.uk Last Revision Date: February 12, 2006 Version 1.0 Table of Contents 1. Introduction (Summation) 2. The Principle of Induction 3. Further Examples 4. Final Quiz Solutions to Exercises Solutions to Quizzes The full range of these packages and some instructions, should they be required, can be obtained from our web page Mathematics Support Materials. Section 1: Introduction (Summation) 3 1. Introduction (Summation) Proof by induction involves statements which depend on the natural numbers, n = 1 , 2 , 3 , . . . . It often uses summation notation which we now briefly review before discussing induction itself. We write the sum of the natural numbers up to a value n as: 1 + 2 + 3 + ··· + ( n- 1) + n = n X i =1 i . The symbol ∑ denotes a sum over its argument for each natural number i from the lowest value, here i = 1 , to the maximum value, here i = n . Example 1: Write out explicitly the following sums: a) 6 X i =3 i , b) 3 X i =1 (2 i + 1) , c) 4 X i =1 2 i . Section 1: Introduction (Summation) 4 The above sums when written out are: a) 6 X i =3 i = 3 + 4 + 5 + 6 , b) 3 X i =1 (2 i + 1) = (2 × 1 + 1) + (2 × 2 + 1) + (2 × 3 + 1) = 3 + 5 + 7 , c) 4 X i =1 2 i = 2 1 + 2 2 + 2 3 + 2 4 . It is important to realise that the choice of symbol for the variable we are summing over is arbitrary, e.g., the following two sums are identical: 4 X i =1 i 3 = 4 X j =1 j 3 = 1 3 + 2 3 + 3 3 + 4 3 . The variable that is summed over is called a dummy variable . Section 1: Introduction (Summation) 5 Quiz Select from the answers below the value of 5 X i =2 2 i . (a) 1024 , (b) 62 , (c) 60 , (d) 32 . Exercise 1. Expand the sums (click on the green letters for solutions): (a) 3 X i =1 (2 i- 1) , (b) 4 X j =1 (2 j- 1) , (c) 4 X s =1 10 s , (d) 3 X j =1 12 j , (e) 3 X i =0 3(2 i + 1) , (f) 3 X j =1 1 j 2 . Exercise 2. Express the following in summation notation. (a) 1 + 20 + 400 + 8 , 000 , (b)- 3- 1 + 1 + 3 + 5 + 7 . Hint: write a) as a sum of powers of 20 . Section 2: The Principle of Induction 6 2. The Principle of Induction Induction is an extremely powerful method of proving results in many areas of mathematics. It is based upon the following principle. The Induction Principle: let P ( n ) be a statement which involves a natural number n , i.e., n = 1 , 2 , 3 . . . , then P ( n ) is true for all n if a) P (1) is true, and b) P ( k ) ⇒ P ( k + 1) for all natural numbers k . The standard analogy to this involves a row of dominoes: if it is shown that toppling one domino will make the next fall over (step b) and that the first domino has fallen (step a) then it follows that all of the dominoes in the row will fall over....
View Full Document

This note was uploaded on 01/10/2011 for the course EE 100 taught by Professor Razasuleman during the Spring '10 term at University of Engineering & Technology.

Page1 / 34

induction - Intermediate Mathematics Proof by Induction R...

This preview shows document pages 1 - 7. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online